The gut microbiome of Madagascar’s lemurs from forest fragments in the central highlands - Lydia K. Greene; Tsinjo Andriatiavina; Elissa D. Foss; Ando Andriantsalohimisantatra; Tahiry V. Rivoharison; Fenonirina Rakotoarison; Tiana Randriamboavonjy; Anne D. Yoder; Fanomezana Ratsoavina; Marina B. Blanco (Primates, 2025)

Seasonal Frugivory Modulates the Gut Microbiome of Captive Dwarf Lemurs (Cheirogaleus medius) During Fattening - Arielle Y. Kim; Lydia K. Greene; Anne D. Yoder; Marina B. Blanco (International Journal of Primatology, 2025)

Identification of diverse papillomaviruses in captive black-and-white ruffed lemurs (Varecia variegata) - Elise N. Paietta; Simona Kraberger; Joy M. Custer; Karla L. Vargas; Koenraad Van Doorslaer; Anne D. Yoder; Arvind Varsani (Archives of Virology, 2023)

Population genomic structure in Goodman's mouse lemur reveals long‐standing separation of Madagascar's Central Highlands and eastern rainforests - George P. Tiley; Tobias van Elst; Helena Teixeira; Dominik Schüßler; Jordi Salmona; Marina B. Blanco; José M. Ralison; Blanchard Randrianambinina; Rodin M. Rasoloarison; Amanda R. Stahlke; Paul A. Hohenlohe; Lounès Chikhi; et al. (Molecular Ecology, 2022)
Madagascar's Central Highlands are largely composed of grasslands, interspersed with patches of forest. The historical perspective was that Madagascar's grasslands had anthropogenic origins, but emerging evidence suggests that grasslands were a component of the pre‐human Central Highlands vegetation. Consequently, there is now vigorous debate regarding the extent to which these grasslands have expanded due to anthropogenic pressures. Here, we shed light on the temporal dynamics of Madagascar's vegetative composition by conducting a population genomic investigation of Goodman's mouse lemur ( Microcebus lehilahytsara ; Cheirogaleidae). These small‐bodied primates occur both in Madagascar's eastern rainforests and in the Central Highlands, making them a valuable indicator species. Population divergences among forest‐dwelling mammals will reflect changes to their habitat, including fragmentation, whereas patterns of post‐divergence gene flow can reveal formerly wooded migration corridors. To explore these patterns, we used RADseq data to infer population genetic structure, demographic models of post‐divergence gene flow, and population size change through time. The results offer evidence that open habitats are an ancient component of the Central Highlands, and that widespread forest fragmentation occurred naturally during a period of decreased precipitation near the last glacial maximum. Models of gene flow suggest that migration across the Central Highlands has been possible from the Pleistocene through the recent Holocene via riparian corridors. Though our findings support the hypothesis that Central Highland grasslands predate human arrival, we also find evidence for human‐mediated population declines. This highlights the extent to which species imminently threatened by human‐mediated deforestation may already be vulnerable from paleoclimatic conditions.

Gut Microbial Diversity and Ecological Specialization in Four Sympatric Lemur Species Under Lean Conditions - Lydia K. Greene; Elodi Rambeloson; Hoby A. Rasoanaivo; Elissa D. Foss; Anne D. Yoder; Christine M. Drea; Marina B. Blanco (International Journal of Primatology, 2021)

The challenge and promise of estimating the de novo mutation rate from whole‐genome comparisons among closely related individuals - Anne D. Yoder; George P. Tiley (Molecular Ecology, 2021)
Germline mutations are the raw material for natural selection, driving species evolution and the generation of earth's biodiversity. Without this driver of genetic diversity, life on earth would stagnate. Yet, it is a double‐edged sword. An excess of mutations can have devastating effects on fitness and population viability. It is therefore one of the great challenges of molecular ecology to determine the rate and mechanisms by which these mutations accrue across the tree of life. Advances in high‐throughput sequencing technologies are providing new opportunities for characterizing the rates and mutational spectra within species and populations thus informing essential evolutionary parameters such as the timing of speciation events, the intricacies of historical demography, and the degree to which lineages are subject to the burdens of mutational load. Here, we will focus on both the challenge and promise of whole‐genome comparisons among parents and their offspring from known pedigrees for the detection of germline mutations as they arise in a single generation. The potential of these studies is high, but the field is still in its infancy and much uncertainty remains. Namely, the technical challenges are daunting given that pedigree‐based genome comparisons are essentially searching for needles in a haystack given the very low signal to noise ratio. Despite the challenges, we predict that rapidly developing methods for whole‐genome comparisons hold great promise for integrating empirically derived estimates of de novo mutation rates and mutation spectra across many molecular ecological applications.

Living in tiny fragments: a glimpse at the ecology of Goodman’s mouse lemurs (Microcebus lehilahytsara) in the relic forest of Ankafobe, Central Highlands, Madagascar - Jean-Basile Andriambeloson; Marina B. Blanco; Ando Andriantsalohimisantatra; Tahiry V. Rivoharison; Nathan Walker; Chris Birkinshaw; Anne D. Yoder (Primates, 2021)

Next-generation technologies applied to age-old challenges in Madagascar - Marina B. Blanco; Lydia K. Greene; Fidisoa Rasambainarivo; Elizabeth Toomey; Rachel C. Williams; Lanto Andrianandrasana; Peter A. Larsen; Anne D. Yoder (Conservation Genetics, 2020)
Madagascar is a biodiversity hotspot that is facing rapid rates of deforestation, habitat destruction, and poverty. Urgent action is required to document the status of biodiversity to facilitate efficacious conservation plans. With the recent advent of portable and affordable genetic technologies, it is now possible to take genomic approaches out of the lab and into the field. Mobile genetics labs can produce scientifically reproducible data under field conditions, dramatically minimizing the time between sample collection and data analysis. Here, we show “proof of concept” by deploying miniPCR bio’s miniaturized thermal cycler alongside Oxford Nanopore’s MinION DNA sequencer in Madagascar. Specifically, we deployed this technology at Anjajavy, northwestern Madagascar for rapid biodiversity assessment. We successfully extracted mouse lemur DNA, amplified and sequenced a phylogenetically informative mitochondrial gene (cytochrome-b; cytb), and thereby confirmed the presence of Danfoss’ mouse lemur ( M. danfossi ) within the Anjajavy Reserve. We show that a mobile genetics lab can provide expeditious results, and allow scientists to conduct genetic analyses, potentially allowing for rapid interventions under emergency conditions in situ. Additionally, mobile labs offer powerful training opportunities for in-country scientists for whom training opportunities were previously confined to ex-situ locations. By bringing genomic technologies to Madagascar and other economically challenged and biodiverse regions of the world, the next generation of scientists and conservationists can more fully implement their leadership roles. Local laboratory and training facilities are changing the polarity of research programs in Madagascar and empowering national researchers to take charge of environmental stewardship.

Warning SINEs: Alu elements, evolution of the human brain, and the spectrum of neurological disease - Peter A. Larsen; Kelsie E. Hunnicutt; Roxanne J. Larsen; Anne D. Yoder; Ann M. Saunders (Chromosome Research, 2018)

Transcriptomics in the wild: Hibernation physiology in free‐ranging dwarf lemurs - Sheena L. Faherty; José Luis Villanueva‐Cañas; Marina B. Blanco; M. Mar Albà; Anne D. Yoder (Molecular Ecology, 2018)
Hibernation is an adaptive strategy some mammals use to survive highly seasonal or unpredictable environments. We present the first investigation on the transcriptomics of hibernation in a natural population of primate hibernators: Crossley's dwarf lemurs ( Cheirogaleus crossleyi ). Using capture–mark–recapture techniques to track the same animals over a period of 7 months in Madagascar, we used RNA‐seq to compare gene expression profiles in white adipose tissue (WAT) during three distinct physiological states. We focus on pathway analysis to assess the biological significance of transcriptional changes in dwarf lemur WAT and, by comparing and contrasting what is known in other model hibernating species, contribute to a broader understanding of genomic contributions of hibernation across Mammalia. The hibernation signature is characterized by a suppression of lipid biosynthesis, pyruvate metabolism and mitochondrial‐associated functions, and an accumulation of transcripts encoding ribosomal components and iron‐storage proteins. The data support a key role of pyruvate dehydrogenase kinase isoenzyme 4 ( PDK4 ) in regulating the shift in fuel economy during periods of severe food deprivation. This pattern of PDK4 holds true across representative hibernating species from disparate mammalian groups, suggesting that the genetic underpinnings of hibernation may be ancestral to mammals.

The effect of body mass and diet composition on torpor patterns in a Malagasy primate (Microcebus murinus) - Sheena L. Faherty; C. Ryan Campbell; Susan A. Hilbig; Anne D. Yoder (Journal of Comparative Physiology B, 2017)

Population and Conservation Genetics in an Endangered Lemur, Indri indri, Across Three Forest Reserves in Madagascar - Schyler O. Nunziata; Peter Wallenhorst; Meredith A. Barrett; Randall E. Junge; Anne D. Yoder; David W. Weisrock (International Journal of Primatology, 2016)

Species discovery and validation in a cryptic radiation of endangered primates: coalescent‐based species delimitation in M adagascar's mouse lemurs - Scott Hotaling; Mary E. Foley; Nicolette M. Lawrence; Jose Bocanegra; Marina B. Blanco; Rodin Rasoloarison; Peter M. Kappeler; Meredith A. Barrett; Anne D. Yoder; David W. Weisrock (Molecular Ecology, 2016)
Implementation of the coalescent model in a Bayesian framework is an emerging strength in genetically based species delimitation studies. By providing an objective measure of species diagnosis, these methods represent a quantitative enhancement to the analysis of multilocus data, and complement more traditional methods based on phenotypic and ecological characteristics. Recognized as two species 20 years ago, mouse lemurs (genus Microcebus ) now comprise more than 20 species, largely diagnosed from mt DNA sequence data. With each new species description, enthusiasm has been tempered with scientific scepticism. Here, we present a statistically justified and unbiased Bayesian approach towards mouse lemur species delimitation. We perform validation tests using multilocus sequence data and two methodologies: (i) reverse‐jump Markov chain Monte Carlo sampling to assess the likelihood of different models defined a priori by a guide tree, and (ii) a Bayes factor delimitation test that compares different species‐tree models without a guide tree. We assess the sensitivity of these methods using randomized individual assignments, which has been used in bpp studies, but not with Bayes factor delimitation tests. Our results validate previously diagnosed taxa, as well as new species hypotheses, resulting in support for three new mouse lemur species. As the challenge of multiple researchers using differing criteria to describe diversity is not unique to Microcebus , the methods used here have significant potential for clarifying diversity in other taxonomic groups. We echo previous studies in advocating that multiple lines of evidence, including use of the coalescent model, should be trusted to delimit new species.

Two New Species of Mouse Lemurs (Cheirogaleidae: Microcebus) from Eastern Madagascar - Rodin M. Rasoloarison; David W. Weisrock; Anne D. Yoder; Daniel Rakotondravony; Peter M. Kappeler (International Journal of Primatology, 2013)

Defining spatial and temporal patterns of phylogeographic structure in Madagascar’s iguanid lizards (genus Oplurus ) - LAUREN M. CHAN; DEAN CHOI; ACHILLE P. RASELIMANANA; HERY A. RAKOTONDRAVONY; ANNE D. YODER (Molecular Ecology, 2012)
Understanding the remarkably high species diversity and levels of endemism found among Madagascar’s flora and fauna has been the focus of many studies. One hypothesis that has received much attention proposes that Quaternary climate fluctuations spurred diversification. While spatial patterns of distribution and phylogenetic relationships can provide support for biogeographic predictions, temporal estimates of divergence are required to determine the fit of these geospatial patterns to climatic or biogeographic mechanisms. We use multilocus DNA sequence data to test whether divergence times among Malagasy iguanid lizards of the subfamily Oplurinae are compatible with a hypotheses of Pliocene–Pleistocene diversification. We estimate the oplurine species tree and associated divergence times under a relaxed‐clock model. In addition, we examine the phylogeographic structure and population divergence times within two sister species of Oplurus primarily distributed in the north‐west and south‐west of Madagascar ( Oplurus cuvieri and Oplurus cyclurus , respectively). We find that divergence events among oplurine lineages occurred in the Oligocene and Miocene and are thus far older and incompatible with the hypothesis that recent climate fluctuations are related to current species diversity. However, the timing of intraspecific divergences and spatial patterns of population genetic structure within O. cuvieri and O. cyclurus suggest a role for both intrinsic barriers and recent climate fluctuations at population‐level divergences. Integrating information across spatial and temporal scales allows us to identify and better understand the mechanisms generating patterns diversity.

Divergence dates for Malagasy lemurs estimated from multiple gene loci: geological and evolutionary context - Anne D. Yoder; Ziheng Yang (Molecular Ecology, 2004)
The lemurs of Madagascar are a unique radiation of primates that show an extraordinary diversity of lifestyles, morphologies and behaviours. However, very little is known about the relative antiquity of lemuriform clades due to the lack of terrestrial fossils for the Tertiary of Madagascar. Here, we employ a Bayesian method to estimate divergence dates within the lemuriform radiation using several unlinked gene loci and multiple fossil calibrations outside the lemuriform clade. Two mitochondrial genes (cytochrome oxidase II and cytochrome b ), two nuclear introns (transthyretin intron 1 and von Willebrand factor gene intron 11) and one nuclear exon (interphotoreceptor retinoid binding protein, exon 1) are used in separate and combined analyses. The genes differ in taxon sampling and evolutionary characteristics but produce congruent date estimates. Credibility intervals narrow considerably in combined analyses relative to separate analyses due to the increased amount of data. We also test the relative effects of multiple vs. single calibration points, finding that, when only single calibration points are employed, divergence dates are systematically underestimated. For the mitochondrial DNA data set, we investigate the effects of sampling density within the mouse lemur radiation (genus Microcebus ). When only two representative species are included, estimated dates throughout the phylogeny are more recent than with the complete‐species sample, with basal nodes less affected than recent nodes. The difference appears to be due to the manner in which priors on node ages are constructed in the two analyses. In nearly all analyses, the age of the lemuriform clade is estimated to be approximately 62–65 Ma, with initial radiation of mouse lemurs and true lemurs (genus Eulemur ) occurring approximately 8–12 Ma. The antiquity of the mouse lemur radiation is surprising given the near uniform morphology among species. Moreover, the observation that mouse lemurs and true lemurs are of similar ages suggests discrepancies in rates of morphological, behavioural and physiological evolution in the two clades, particularly with regard to characteristics of sexual signalling. These differences appear to correlate with the nocturnal vs. diurnal lifestyles, respectively, of these two primate groups.

Molecular Evidence of Reproductive Isolation in Sympatric Sibling Species of Mouse Lemurs - Anne D. Yoder; Melissa M. Burns; Fabien Génin (International Journal of Primatology, 2002)